(untitled) (Eurasian Journal of Engineering and Technology, 2023)
This article seeks to give a general overview of the techniques researchers have employed to enhance the efficiency of Sequencing Batch Biofilm Reactor (SBBR) in domestic sewage treatment. One of the most recent uses of sequencing batch reactor treatment technology is the sequencing batch biofilm reactor (SBBR), which is created when the SBR is paired with biofilm development on the surface of the support material. The assessment of the available literature conducted here demonstrates the effectiveness and adaptability of this technique for the removal of phosphorus, nitrogen, and organic materials under diverse environmental conditions. The review contains pertinent laboratory experiments that were conducted